ADVANTAGES AND DISADVANTAGES OF DISTANCE LEARNING IN UKRAINIAN HIGHER EDUCATION INSTITUTIONS UNDER MARTIAL LAW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Since 2020, due to objective reasons (first the Covid-19 pandemic, then the war), many Ukrainian educational institutions have not been able to organize a systematic educational process in a face-to-face format. Educational institutions have to combine different forms of education in order to establish effective interaction and ensure high-quality acquisition of knowledge. In the conditions of quarantine restrictions, and later martial law in Ukraine, the distance form turned out to be the most optimal and safest option for organizing education. The article examines the advantages and disadvantages of distance learning based on a survey of applicants for a bachelor's degree who are studying in the specialty 012 Preschool Education at Vinnytsia State Pedagogical University. A total of 53 applicants who have been studying using distance learning technologies for 4 years were surveyed. The following questions were investigated: what difficulties did students encounter at the beginning of distance learning, how did they overcome them; dynamics of attitude towards distance learning (over four years of study); analyzed the difficulties (and psychological ones, in particular) that applicants faced, and how they solved them. The advantages of distance learning were the opportunity to spend more time with family, save time traveling to the university, mobility of learning (the ability to study anywhere at any time). Disadvantages: lack of "live" communication and technical problems that arose during distance learning. In the course of this study, we used the following methods: theoretical: analysis of scientific sources to determine the state of research on the problem of organizing distance learning in Ukrainian and foreign higher education institutions. The synthesis, systematization and generalization of theoretical provisions of the problem were used; empirical: pedagogical observation of the organization of distance learning at the Vinnytsia State Pedagogical University named after Mykhailo Kotsiubynskyi of students of the specialty 012 Preschool Education, conversations with teachers of the Department of Preschool Education of this university, conversations with 4th-year students of the specialty 012 Preschool Education of full-time and correspondence studies. The survey lasted 8 days: from September 9 to 16, 2024. Participation in the online survey was voluntary. To increase the effectiveness of distance learning, it is recommended to increase the digital competence of teachers of higher education institutions in the use of various digital tools and a humanistic orientation to create a more comfortable environment. The features of using BYOD technology ("bring your own device") in conditions of distance learning are noted.